If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(1 + 5r) = 23 + r (1 * 4 + 5r * 4) = 23 + r (4 + 20r) = 23 + r Solving 4 + 20r = 23 + r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1r' to each side of the equation. 4 + 20r + -1r = 23 + r + -1r Combine like terms: 20r + -1r = 19r 4 + 19r = 23 + r + -1r Combine like terms: r + -1r = 0 4 + 19r = 23 + 0 4 + 19r = 23 Add '-4' to each side of the equation. 4 + -4 + 19r = 23 + -4 Combine like terms: 4 + -4 = 0 0 + 19r = 23 + -4 19r = 23 + -4 Combine like terms: 23 + -4 = 19 19r = 19 Divide each side by '19'. r = 1 Simplifying r = 1
| 7x(x-1)=28 | | 4w^2+7w=-3 | | 4x*2+3x=3x*2-4x+18 | | -8r^2+9=6r | | 3x+1+x=49 | | 7+4x=-8+7(1+5x) | | -7(2(-5)+4)+10(-5)-9= | | 31-5x=10-8x | | 4y^2+11y+7=0 | | 4(2b-4)=2(a-5) | | 10x+y=-8 | | 4x+4=-8+5x | | 2=x-(-43) | | a^2x+x-1=a-2ax | | -x+35=3x+11 | | 36+8a=(3a+1) | | (3x-4)+(X)=148 | | -2+2x=5x-20 | | 7x+9=49+3x | | 25x^2-24x-9=-7x^2+12-18 | | 6=x/65 | | 2x-6=7x+14 | | 4x+14=-8x-2(7-4x) | | 36+8a=3(3a+1) | | -5x-9y=45 | | x-6=2x+5 | | 5-7(8y+6)= | | 11(2-9)+99-10(2)= | | 13k-130=201 | | 3x+5=-19+7x | | x-5=2x+5 | | -37/16=v/32 |